Causes and trends of under-five mortality in the Gilgel Gibe Health and Demographic Surveillance System, 2005 to 2019, Southwest Ethiopia: Cohort study - Desalegn Shiferaw; Mohammed Sanni Ali; Fasil Tessema; Bikila Regassa Feyisa; Mubarek Yesse Ashemo; Assefa Legesse Sisay; Muluemebet Abera; Tizta Tilahun Degfie; Esayas Alemayehu; Chaltu Fikru; Yohannes Kebede; Lelisa Sena Dadi (PLoS ONE, 2026)
Background Irrespective of intensive global efforts to reduce under-five mortality, it remains a significant public health concern. Understanding the causes and trends of under-five mortality is essential for guiding targeted interventions, assessing the effectiveness of public health strategies, and monitoring changes in mortality over time. The health and demographic surveillance system is one of the preferred sources to study the cause of under-five mortality. Objective This study aims to analyse the causes and trends of under-five deaths in Southwest Ethiopia using Gilgel-Gibe Health and Demographic Surveillance System (GGHDSS) database. Methods GGHDSS is an open, dynamic cohort that was established in 2005. Fifteen years of mortality data and seven years of Verbal Autopsy (VA) data were extracted from the GGHDSS database for this study. The VA data are part of the fifteen year mortality dataset, in which causes of death were determined through the VA method. After extracting the data from MYSQL and OpenHDS, it was exported to Excel for further cleaning. Finally, the cleaned data were exported to R statistical software for analysis and visualization. Neonatal, infant, and under-five mortality trends were analysed and the proportion of cause specific deaths were identified from the VA data. Results Between 2005 and 2019, 28, 811 children, 13931 (48.35%) female and 14880 (51.65%) male, were born alive and registered in the GGHDSS, among which 1828 (6.34%) of them died before celebrating their fifth birthday. The overall under-five mortality rate was 63.4 (95% CIs; 60.6, 66.3) per 1000 live births while neonatal and infant mortality rates were 30(95% CIs; 28.1, 32) and 50.2 (95% CIs; 47.6, 52.7), respectively. The mortality rate during the surveillance years showed a declining trend among neonatal, infant, and overall under-five children, with average slopes of −2.49, −4.56, and −7.24, respectively. From 1070 under-five deaths captured by the VA method in GGHDSS during 2009–2016, 596 (55.7%) were male and 474 (44.30%) were female. The most common causes of neonatal death were birth asphyxia and perinatal respiratory disorders, bacterial sepsis, and prematurity including respiratory distress. In the post-neonatal period, the most common causes of death were acute lower respiratory infections (including pneumonia and acute bronchitis), intestinal infectious diseases including diarrheal diseases, and malaria. Severe malnutrition, intestinal infectious diseases, and acute lower respiratory infections were responsible for more than half of the deaths among children between 12 and 59 months of age. Conclusions Under-five mortality has shown a significant declining trend between 2005 and 2019 at the study setting. Birth asphyxia, neonatal infections, and prematurity were among the most common causes of neonatal deaths, whereas infectious diseases and malnutrition were the main causes of death beyond the neonatal period. Strengthening perinatal and neonatal care, improving prevention and management of childhood infections, and enhancing early nutritional interventions are needed to reduce under-five mortality.